The Influence Of Stockbit Application Quality On Custome Satisfaction In Medan City - Tambunan, Sarah Rouli; Tarigan, Mila Delvana (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the effect of Stockbit App quality on customer satisfaction in Medan City. Good application quality is believed to play an important role in increasing customer satisfaction, especially in today's digital era. The dominance of Stockbit users comes from Gen Z, indicating the app's popularity among young people. The Stockbit app features advanced features such as a stock screener. This study aims to determine the effect of application quality on customer satisfaction partially and simultaneously. The population in this study were Stockbit customers in Medan City aged 17-27 years. The number of samples in this study were 100 people taken using nonprobability sampling technique. This type of research is quantitative research with data collection techniques carried out through questionnaires. The data analysis methods in this study are validity test, reliability test, classical assumption test, multiple linear regression test, and hypothesis testing. From the results of this study, it was obtained that 57.8% of Stockbit Sekuritas customer satisfaction was influenced by application quality, while 42.2% of Stockbit Sekuritas customer satisfaction was influenced by other variables not examined in this study. The results of this study indicate that partially application quality has a positive and significant effect on Stockbit Sekuritas customer satisfaction in Medan City.